2017
DOI: 10.1007/s11695-017-2844-x
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Prolonged Length of Hospital Stay and Readmissions After Laparoscopic Sleeve Gastrectomy and Laparoscopic Roux-en-Y Gastric Bypass

Abstract: BackgroundLaparoscopic sleeve gastrectomy (LSG) and laparoscopic gastric bypass (LRYGB) are most commonly performed bariatric procedures. Laparoscopic approach and enhanced recovery after surgery (ERAS) protocols managed to decrease length of hospital and morbidity. However, there are patients in whom, despite adherence to the protocol, the length of stay (LOS) remains longer than targeted. This study aimed to assess potential risk factors for prolonged LOS and readmissions.MethodsThe study was a prospective o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 52 publications
2
26
1
1
Order By: Relevance
“…Postoperative complications are considered as a distinct factor that affects length of hospital stay. However, recent trials have questioned this statement concerning hospitalization after bariatric procedures [ 50 ]. According to a retrospective analysis of 2629 patients submitted to LSG by Jakob et al [ 51 ], hospital stay beyond 24 hours is not obligatory, under the condition that there are no signs of bleeding and leak or symptoms of vomiting and nausea.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative complications are considered as a distinct factor that affects length of hospital stay. However, recent trials have questioned this statement concerning hospitalization after bariatric procedures [ 50 ]. According to a retrospective analysis of 2629 patients submitted to LSG by Jakob et al [ 51 ], hospital stay beyond 24 hours is not obligatory, under the condition that there are no signs of bleeding and leak or symptoms of vomiting and nausea.…”
Section: Discussionmentioning
confidence: 99%
“…(2013*). Recent reviews have commented on the early postoperative dietary strategy . Patients should be allowed to start drinking clear liquids the night of surgery.…”
Section: Executive Summarymentioning
confidence: 99%
“…Utilizing continuous noninvasive measurements of fluid status, such as the PVI, stroke volume variation, or other technologies, results in less fluid administration during bariatric surgery than empiric calculations of volume requirements or by monitoring urine output . Administration of excess IV fluids can increase the rate of postoperative nausea and length of stay after surgery . To decrease the chances of preoperative dehydration, patients should be allowed to drink clear liquids up to 2 hours prior to surgery.…”
Section: Executive Summarymentioning
confidence: 99%
“…In their study that included 492 patients, their definition of prolonged hospital stay post-LSG was > 3 days. They found that 29.47% of all patients needed a prolonged stay [9]. So, and considering the 9.2% figure found in KFSH bariatric centre, the ALOS at KFSH is not unusual.…”
Section: Cost and Length Of Hospital Staymentioning
confidence: 89%